Electric field control of nonvolatile two‐state magnetoelectric coefficient at room temperature in a hexaferrite. Issue 8 (24th March 2020) - Zhai, Kun; Lu, Peipei; Chang, Yanfen; Nie, Anmin; Yu, Zhipeng; Sun, Young
Abstract: Cross coupling between magnetization and polarization in multiferroic materials provides a new controlling dimension for creating novel electric devices, particularly the electrical writing magnetic reading of low‐power consumption nonvolatile random access memory. Despite its importance, rare single‐phase materials that exhibit significant magnetoelectric phenomena at room temperature exist. We herein report that a spin‐driven multiferroic hexaferrite Ba1.1 Sr0.9 Co2 Fe11 AlO22 exhibits a prominent direct and converse magnetoelectric effect at room temperature. The electric field can manipulate magnetization as large as 0.1 µB /f.u. in the range of ±1 MV/m without any external magnetic field. Moreover, a feasible nonvolatile memory based on polycrystalline Ba1.1 Sr0.9 Co2 Fe11 AlO22 is realized by recording the states of magnetoelectric coefficients, which is promising for further application in magnetoelectric electronics.